Malignant retroperitoneal fibrosis Rectal, duodenal and ureteral occlusion - Rodríguez, Gustavo; Navarrete, Héctor; Bruno, Gerardo; Malfatto, Gustavo; Praderi, Raúl (Cirugía del Uruguay, 1995)
The authors present two clinical observations of retroperitoneal malignan/ fibrosis; one of them was secondary to breast cancer and the other to cancer of the panchreas. Both cases presented rectal, duodenal and ureteral occlusion. They were treated by means of gastroenterostomy, colostomy, ureterostomy and pyelostomy. A survival of six month was obtained in one of the cases.